An Analysis of Online English Learning Through Messenger Application at SMAN 1 Tinambung - Andi Mega Januarti Putri; Rani Suhartini; Amrang Amrang (TEKSTUAL, 2021)
The purpose of this study was to analyze the learning process and student responses to online English learning through the messenger application at SMAN 1 Tinambung, by analyzing the learning process. This research is a qualitative descriptive study. Data collection techniques were observation, interviews and documentation. Researcher took 2 classes at SMAN 1 Tinambung as research subjects, class XII MIA 4 as subjects in the learning process and XII IIS 4 total 24 students as respondents to the learning process through messenger applications. The researcher chose class XII IIS 4 as the respondent because the researcher saw that class XII IIS 4 each student had a different character and was more responsive in giving answers. The results showed that the process of learning English online through the messenger application was inefficient, meaning that the process of learning English through the messenger application could not help students understand learning through the messenger application. Furthermore, the student's response to learning English using the messenger application, from 8 questions in the interview showed that the student's response to learning English using the messenger application was inefficient because they could not understand the learning material taught through the messenger application. In this case, the researcher assessed that the online English learning process through the messenger application was inefficient in learning. In addition, students also sometimes have difficulty learning to use messenger applications.